Association between quality of life with depressive symptoms, anxiety, stress and emotional distress in Peruvian cancer patients: a cross-sectional study - Malaquias-Obregon, Sofía C (2026)
Introduction: Cancer patients frequently experience psychological symptoms such as depression, anxiety, perceived stress, and emotional distress, which may negatively affect their quality of life. However, the impact of comorbid mental health symptoms on both mental and physical components of quality of life remains insufficiently explored in Latin American populations. Objective: To determine the association between depressive symptoms, anxiety, stress, and emotional distress (exposures) and quality of life (outcome) in Peruvian cancer patients. Method: A cross-sectional study was conducted among 465 adult cancer patients recruited from oncology services. Mental health variables were dichotomized according to established cut-off points. Quality of life (mental and physical components) was categorized into low–medium versus high levels. Generalized linear models with Poisson distribution and robust variance were used to estimate crude and adjusted prevalence ratios (PR) with 95% confidence intervals. Results: A prevalence of anxious symptoms of 27.5%, depressive symptoms of 20.4%, symptoms of moderate-severe stress of 83.2%, and emotional discomfort of 57.4% were identified. Regarding the Poisson regression model, cancer patients with 12 or more years of education were less likely to have symptoms of emotional distress. Moderate to severe depressive symptoms, anxiety, stress, and emotional distress were significantly associated with low–medium mental quality of life. Comorbidity of psychological symptoms showed a stronger association with impaired mental quality of life compared to individual symptoms. Conclusions: Emotional distress and stress were found to be the main variables associated with both physical and mental quality of life. Other variables associated with mental health problems include a high level of education. Finally, it was found that lower quality of life (both mental and physical) is associated with greater comorbidity of mental health problems.